Fatores determinantes do tamanho corporal, forma do crânio e uso do espaço em mamíferos sul-americanos (Laurasiatheria), com ênfase em felídeos - Machado, Renata Figueira (2017)
The characteristics of animals show similarities or differences according to the environment in which they are inserted and result in selection of characters that determine them, differentiating them phenotypically. Ecogeographic studies show the existence of differences in skull shape of species occurring between stable and seasonal regions, and also the existence of a latitudinal gradient. In a second approach, some physiological and ecological factors of animals, such as body mass and sex, can influence the home range size of animals. The objective of this study was to analyze the variations in the skull size and shape of the South American mammalian belonging to Laurasiatheria superorder, with a wide geographic distribution that occur in open and closed biomes of South America; verify the existence of latitudinal cline in the morphological variation and if factors such as body mass, sex and biome affect the home range size of felids. To answer these questions, 515 specimens were photographed in six South American museums and literature data were collected on body mass and mean of home ranges of 19 species of felids and body mass, home range, sex and biome of three species of felids. Through geometric morphometric procedures and univariate and multivariate statistical analyzes it was possible to verify that the environment in which the animal is inserted can be considered as a factor of differentiation of the skull size and shape of some species of South American mammals that are inside and outside the Amazon Forest. Species of Procyonidade and Phyllostomidae in South America showed larger body sizes in open biomes than in closed biomes. The skull shape of the males and females of the Procyonidade and Phyllostomidae and females of Felidae presented greater complexity in open biomes. It was verified the influence of allometry in the skull shape of most species. The representative of the family Phyllostomidae was the specie that most differentiated in the transition between open and closed biome. There are differences in skull size and shape, and influence of allometry to the species Panthera onca, Leopardus pardalis and Puma concolor. In relation to the space, the skull size presents a more expressive variation than skull shape, as for the climate, both skull size and shape presented significant variation for the three species of felids studied here. The home range size of felids was positively correlated with body mass, regardless of phylogeny. At the intraspecific level, both body mass and home range of males are higher than females for P. onca, L. pardalis and P. concolor. The home range size of P. onca increases in open habitats. The body mass of P. onca is greater in open areas.